PELAYANAN KESEHATAN MASYARAKAT DI RUMAH SAKIT UMUM DAERAH DOKTER SOEDARSO PONTIANAK KALIMANTAN BARAT - Lilyana Sihombing E.01108014 (FISIP Universitas Tanjungpura, 2012)
AbstractThe title of research is Health Service at Soedarso Hospital, Pontianak West Borneo. The purposeof this research is to give understanding about healthy service of the citizen through the guaranteeof healthy service. In case that there are still many citizen complain about the quality of healthyservice that given by the hospital in order to increase the quality of the service to reach themaximum servive. The method of this research is descriptive and the technique is qualitative dataanalysis. In this research, the service of citizen healthy includes three thing, those aretranspalation, partisipasion, and the equivalence of the rights. The result of data analysis show thelack of information and the clear guidance from the employer about the enviropment, the lack ofthe enviropment’s cleaness and the security, and also the lack of the attention from health centreemployer in giving the service for the patiens.Keywords : healthy service, jamkesmas program, transparation and partisipation.